Combination of the Distance From Tumor Edge to Subventricular Zone and IDH Mutation Predicts Prognosis of Patients With Glioma - Zhang, Shuixian; Zhao, Fengchun; Zhou, Tengyuan; Liu, Dan; Yao, Xiaohong; Fu, Wenjuan; Liu, Zhi; Lan, Chuan; Lai, Zhaopan; Liu, Chen; Li, Haitao; Li, Yuhong; et al. (Frontiers in Oncology, 2021)
Both subventricular zone (SVZ) contact and isocitrate dehydrogenase 1 (IDH1) mutation have been reported to be related to the outcome of glioma, respectively. However, far too little attention has been paid to the role of tumor edge-SVZ distance in the outcome of glioma. We aim to assess the value of tumor-SVZ distance, as well as combined tumor-SVZ distance and IDH status, in predicting the outcome of gliomas (WHO grade II–IV). Here, the MR images and clinical data from 146 patients were included in the current study. The relationship between survival and the tumor-SVZ distance as well as survival and combination of tumor-SVZ distance and IDH status were determined via univariate and multivariate analyses. In univariate analysis of tumor-SVZ distance, the patients were divided into three types (SVZ involvement, tumor-SVZ distance from 0 to 10 mm, and tumor-SVZ distance >10 mm). The results showed that the OS (p = 0.02) and PFS (p = 0.002) for the patients had a positive correlation with the tumor-SVZ distance. In addition, simple linear correlation found a significant relationship between the two parameters (OS and PFS) and tumor-SVZ distance in patients with non-SVZ-contacting glioma. Combination analysis of the tumor-SVZ distance and IDH status showed that IDH1 mutation and SVZ non-involvement enable favorable outcomes, whereas IDH1 wild type with SVZ involvement indicates a significantly worse prognosis in all patients. Moreover, in patients with non-SVZ-contacting glioma, IDH1 mutation concurrent with tumor-SVZ distance >10 mm has better OS and PFS. IDH1 wild type and tumor-SVZ distance from 0 to 10 mm suggest poorer OS and PFS. Multivariate analysis showed WHO grade IV, SVZ involvement, tumor-SVZ distance from 0 to 10 mm, IDH1 mutation, gross total resection, and chemotherapy serve as independent predictors of OS. WHO grade IV, SVZ involvement, tumor-SVZ distance from 0 to 10 mm, IDH1 mutation, and chemotherapy serve as independent predictors of PFS of patients with glioma. In conclusion, tumor-SVZ distance and IDH1 mutation status are the determinants affecting patient outcome.